Synthesis, Biological, Spectral, and Thermal Investigations of Cobalt(II) and Nickel(II) Complexes of N-Isonicotinamido-2′,4′-Dichlorobenzalaldimine - Ram K. Agarwal; Deepak Sharma; Lakshman Singh; Himanshu Agarwal (Bioinorganic Chemistry and Applications)
A new series of 12 complexes of cobalt(II) and nickel(II) with N-isonicotinamido-2′,4′-dichlorobenzalaldimine (INH-DCB) with the general composition MX2⋅n(INH-DCB) [M = Co(II) or Ni(II), X = Cl−, Br−, NO3−, NCS−, or CH3COO−, n = 2; X = ClO4−, n = 3] have been synthesized. The nature of bonding and the stereochemistry of the complexes have been deduced from elemental analyses, infrared, electronic spectra, magnetic susceptibility, and conductivity measurements. An octahedral geometry has been suggested for all the complexes. The metal complexes were screened for their antifungal and antibacterial activities on different species of pathogenic fungi and bacteria and their biopotency has been discussed.